ESG DISCLOSURES AND TECHNOLOGICAL INNOVATION ON THE FINANCIAL PERFORMANCE OF ENERGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - ANTHONY HOLLY; ROBERT JAO (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2026)
Energy companies are frequently exposed to price volatility, which significantly impacts their overall performance. This study examines the influence of Environmental, Social, and Governance (ESG) disclosure and technological innovation on the financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2025. Using secondary data from annual and sustainability reports, this research employs purposive sampling, yielding 68 firm-year observations from 17 selected companies. Data was analyzed using multiple linear regression. The results indicate that ESG disclosure has a positive and significant effect on financial performance, whereas technological innovation does not have a significant impact. These findings provide sector-specific empirical evidence that refines both legitimacy theory and stakeholder theory. Furthermore, the results offer practical implications for managers and policymakers in formulating more resilient disclosure strategies to enhance corporate financial outcomes.